FEVER AS INDICATOR TO SECONDARY INFECTION IN DENGUE VIRAL INFECTION - Soegijanto, Soegeng; Nuryandari, Sufiandika; Churrotin, Siti; Sucipto, Teguh Hari (Institute of Topical Disease Universitas Airlangga, 2018)
Dengue Virus Infections are distributed in tropical and sub-tropical regions and transmitted by the mosquitoes such as Aedes aegypti and Aedes albopictus. Dengue virus can cause dengue fever, dengue hemorrhagic fever and dengue shock syndrome or dengue and severe dengue classified by World Health Organization. Beside it concurrent infection virus salmonella had been found some cases who showed fever more than 7 days. Concurrent infection with two agents can result in an illness having overlapping symptoms creating a diagnostic dilemma for treating physician, such as dengue fever with typhoid fever. The aim of this research is detection of dengue virus and secondary infection with Salmonella typhi in patients suspected dengue virus infection. Detection of dengue virus and Salmonella typhi using immunochromatography test such as NS1, IgG/IgM for dengue virus infection, and IgM/IgG Salmonella and blood culture. The fifty children with dengue virus infection came to Soerya hospital and 17 cases suspected dengue virus infection, five cases showed a positive NS1 on the second day of fever and one case concurrent with clinical manifestation of convulsi on the third days of fever there were five cases only showed positive. It was showed in this study that on the fourth to six day of fever in dengue virus infection accompanied by antibody IgM & IgG dengue. There were 12 cases showed the clinical manifestation of concurrent dengue viral infection and Salmonella, all of them showed a mild clinical manifestation and did not show plasma leakage and shock. In this study we found the length of stay of concurrent Dengue Virus Infection and Salmonella infection is more than 10 days. These patients were also more likely to have co-existing haemodynamic disturbances and bacterial septicaemia which would have required treatment with inotropes and antibiotics. This idea is very important to make update dengue viral management to decrease mortality in outbreak try to gain new prevention method before the occurrence of outbreak.